Mastery Concept of Harmonic Vibration with Meaningful Instructional Design Learning Model through Experimental Methods - Mila Armiati; Ahmad Harjono; Susilawati Susilawati (Jurnal Penelitian Pendidikan IPA, 2020)
This research was aim to identify the effect of meaningful instructional design (MID) learning model through experimental methods on mastering the concept of harmonic vibration. This type of research was quasi experiment with nonequivalent control group design with pre-test and post-test. The population was all students class X MIA SMAN 7 Mataram in the academic year 2018/2019 with a purposive sampling technique. Class X MIA 4 was chosen as the experimental class with MID learning model through the experimental method and class X MIA 5 as the control class with conventional learning. Concept mastery data were analyzed using the polled variance t-test. The results of the analysis were tcount>ttable (4.39 > 2.00) at a significant level of 5% which means that Ha was accepted and H0 was rejected. Concluded that there was the effect of the meaningful instructional design (MID) learning model through the experimental method of mastering the concept of harmonic vibration